The influence of grammatical and semantic functions on the development of linguistic forms, with special reference to the theories of Wilhelm Horn - McConkey, William G (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Litt.) -- Universiteit van Stellenbosch, 1929.